Synthesis and Crystal Structures of Co(II) Complexes Derived From Two Unsymmetrical Bis-Heterocyclic Ligands With Benzimidazole Moiety. Issue 5 (3rd May 2016) - Huang, Jin; Wei, Qin; Zhang, Wen; Zhang, Zhong; Liao, Yong-Zhi
Abstract : Treatment of two kinds of unsymmetrical bis-heterocyclic ligands bearing benzimidazole moiety, 2-[2-(1, 2, 4-triazole-1-yl)ethyl]-1H-benzimidazole (L1 ) and 2-[2-(1, 2, 3-benzotriazole-1-yl)ethyl]-1H-benzimidazole (L2 ), with Co(II) chloride, resulted in two new complexes, [Co3 (L2 )4 Cl6 ]·2H2 O (1 ) and [Co(L1 )Cl2 ]2 (2 ), with different aggregating patterns. Two complexes were characterized by single-crystal X-ray determinations. In the solid state, L1 assumes an anti conformation in compound1, whereas L2 exists as a gauche conformer in compound2 . Complex1 reveals a 1-D double-stranded chain structure consisting of both octahedrally and tetrahedrally coordinated Co(II) ions. Complex2 is a mononuclear tetrahedral Co(II) species, which was hydrogen bonded with each other to give a 1-D linear chain.